Ethnomedicinal Use of Zingiberaceae by the Mentawai Community in Saumanganyak Village, West Sumatra, Indonesia - Linda Wiliana; Erismar Amri; Zikra (UNIVERSITAS PGRI MADIUN, 2025)
The Mentawai Islands, located west of mainland West Sumatra, are part of popp Sumatra Province. The Mentawai people are the indigenous people of the islands and are renowned for their traditional healing practices, practiced by the